The divergent outcome of IL-4Rα signalling on Foxp3 T regulatory cells in listeriosis and tuberculosis - Chia, Julius E.; Rousseau, Robert P.; Ozturk, Mumin; Poswayo, Sibongiseni K. L.; Lucas, Rodney; Brombacher, Frank; Parihar, Suraj P. (Frontiers in Immunology, 2024)
Introduction Forkhead box P3 (Foxp3) T regulatory cells are critical for maintaining self-tolerance, immune homeostasis, and regulating the immune system. Methods We investigated interleukin-4 receptor alpha (IL-4Rα) signalling on T regulatory cells (Tregs) during Listeria monocytogenes (L. monocytogenes) infection using a mouse model on a BALB/c background, specifically with IL-4Rα knockdown in Tregs (Foxp3creIL-4Rα−/lox). Results We showed an impairment of Treg responses, along with a decreased bacterial burden and diminished tissue pathology in the liver and spleen, which translated into better survival. Mechanistically, we observed an enhancement of the Th1 signature, characterised by increased expression of the T-bet transcription factor and a greater number of effector T cells producing IFN-γ, IL-2 following ex-vivo stimulation with heat-killed L. monocytogenes in Foxp3creIL-4Rα-/lox mice. Furthermore, CD8 T cells from Foxp3creIL-4Rα-/lox mice displayed increased cytotoxicity (Granzyme-B) with higher proliferation capacity (Ki-67), better survival (Bcl-2) with concomitant reduced apoptosis (activated caspase 3). In contrast to L. monocytogenes, Foxp3creIL-4Rα-/lox mice displayed similar bacterial burdens, lung pathology and survival during Mycobacterium tuberculosis (M. tuberculosis) infection, despite increased T cell numbers and IFN-γ, TNF and IL-17 production. Conclusion Our results demonstrated that the diminished IL-4Rα signalling on Foxp3+ T regulatory cells resulted in a loss of their functionality, leading to survival benefits in listeriosis but not in tuberculosis.